Optical and Spectroscopic Properties of Rare-Earth-Doped Crystals - Toncelli, Alessandra; Antić, Željka (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is devoted to studying RE-doped bulk and nanocrystalline materials from a scientific point of view and to presenting their possible applications in any field. This reprint is intended to serve as a unique multidisciplinary forum covering all aspects of science, technology and applications of rare-earth-doped crystals, starting from the growth techniques with specific attention to the optical and spectroscopic properties of these materials and their applications.